HUBUNGAN UPAH MINIMUM PROVINSI DENGAN JUMLAH TENAGA KERJA FORMAL DI JAWA TIMUR - DEVI LESTYASARI (Universitas Negeri Surabaya, 2013)
This study aims to find out how the conection of province minimum wage with the number of formal labour. This study is a kind of descriptive associative study with the quantitative approach. This research is done in province East Java with sampel sampel province minimum wage with the number of formal labour in the years 2007-2011. The data analysis technique in this study using product moment correlation with t-test. The result of the study showed that the variable of province minimum wage has a very strong positive conection with the number of formal labour in East Java. While the result of t-test show that txy  ttabel , it means that the research hypothesis is accepted, it means that increased province minimum wage so that increased the number of formal labour too. Keywords: minimum wage, province minimum wage, formal labour.